Application of metal organic framework material in preparation of developing function material, implant intervention material, preparation method of implant intervention material and implant intervention device

By using metal organic frame materials in implant intervention materials, and using its three-dimensional pores and aromatic ring structure to enhance X-ray scattering and absorption, the problems of unsatisfactory imaging effects and degraded mechanical properties of existing implant intervention materials are solved, and the combination of efficient development and excellent mechanical properties is achieved.

CN119587773APending Publication Date: 2025-03-11CHANGCHUN INSTITUTE OF APPLIED CHEMISTRY CHINESE ACADEMY OF SCIENCES
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411910661.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-24
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

The imaging effect of existing implant interventional materials is not ideal in CT scans, and the interface compatibility between polymer materials and contrast agents is poor, resulting in reduced mechanical properties and potential toxic side effects.

Method used

The metal organic frame material is used to form a three-dimensional pore structure and aromatic ring structure through aromatic organic ligand and coordination metal atoms, which enhances the scattering and absorption capacity of X-rays, and prepares the implanted interventional material through solvent-free continuous mechanical method.

Benefits of technology

It significantly improves the X-ray development effect of implant interventional materials, optimizes mechanical properties and biocompatibility, solves the contradiction between imaging effects and mechanical properties, and has environmentally friendly and low cost, which is suitable for industrial large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention relates to the technical field of in-vivo implant intervention composite materials, in particular to application of a metal organic framework material in preparation of a developing function material, an implant intervention material, a preparation method of the implant intervention material and an implant intervention device. The metal organic framework material disclosed by the invention has an enhanced X-ray developing function, can realize regulation and control of mechanical properties of a composite material, and can be applied to preparation of a developing functional material. The implant intervention material provided by the invention comprises a high-molecular polymer matrix and a metal organic framework material doped in the high-molecular polymer matrix, the metal organic framework material comprises an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand; the X-ray developing resolution ratio is high, the mechanical property is good, the biocompatibility is good, and the mechanical property and the processing property of the original polymer matrix can be maintained. Meanwhile, the preparation method is simple and environment-friendly, mild in reaction condition, high in synthesis efficiency and low in cost, and can meet the requirements of industrial large-scale preparation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of in vivo implantable composite materials, in particular to the application of metal organic framework materials in the preparation of developing functional materials, implantable materials and preparation methods thereof, and implantable devices. Background Art

[0002] Polymer materials have the characteristics of plasticity, adjustable mechanical properties, and good biocompatibility, making them a common implantable material and playing an important role in the development of modern medical technology. Common polymer materials include polyurethane elastomers, nylon elastomers, polyethylene, fluorinated ethylene-propylene copolymers, polytetrafluoroethylene, ethylene-tetrafluoroethylene copolymers, etc., which can be used for different types of implantable devices such as heart stents, central venous catheters, and indwelling needles. When implantable devices are used clinically, CT scans are usually required for imaging examinations to determine the location of the device.

[0003] Since the elemental composition of polymer materials is similar to that of human tissues, it is difficult to distinguish them from the human environment after implantation. It is usually necessary to blend high atomic number contrast agents in the polymer matrix to enhance the X-ray attenuation ability and improve the imaging effect. Currently, commonly used iodine-based and barium-based contrast agents such as sodium iothalamate, iopromide, and barium sulfate have poor compatibility with the polymer matrix interface. Too much addition will cause the contrast agent to agglomerate and cause a decrease in mechanical properties, and the precipitation and leakage of the contrast agent may cause certain toxicity and side effects to the human body; too little addition will result in unsatisfactory imaging effects. For example, the amount of barium sulfate added to industrial implantable polyurethane materials is usually less than 20 wt%.

[0004] Therefore, there is an urgent need to develop new materials to achieve a balance between imaging effects and mechanical properties. Summary of the invention

[0005] In view of this, the technical problem to be solved by the present invention is to provide the application of metal organic framework materials in the preparation of development functional materials, implantable interventional materials and their preparation methods and implantable interventional devices. The implantable interventional materials provided by the present invention have X-ray development function, good mechanical properties and processing properties, and good biocompatibility.

[0006] The present invention provides an application of a metal organic framework material in the preparation of a CT contrast agent or an implantable material with an X-ray imaging function, wherein the metal organic framework material comprises an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand;

[0007] The aromatic organic ligand is selected from compounds having a structure of Formula I or Formula II;

[0008] Formula I; Formula II;

[0009] Wherein, the X1 is selected from O or S;

[0010] Said X2 and X3 are independently selected from C or N;

[0011] The R1, R2, R3 and R4 are independently selected from H, a substituted or unsubstituted C1-C5 alkyl group.

[0012] Preferably, the aromatic organic ligand of the present invention is selected from compounds having a structure of Formula Ia or Formula II-a;

[0013] Formula Ia; Formula II-a.

[0014] Preferably, X2 and X3 are different; and R1, R2, R3 and R4 are independently selected from one of hydrogen, methyl and ethyl.

[0015] In certain embodiments of the present invention, the aromatic organic ligand is selected from one or more of 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, 2,5-furandicarboxylic acid dimethyl ester, 2,5-thiophenedicarboxylic acid dimethyl ester, 2,6-pyridinedicarboxylic acid dimethyl ester and 3,5-pyridinedicarboxylic acid dimethyl ester. In certain embodiments of the present invention, the coordinating metal atom is selected from one or more of hafnium, zirconium or bismuth.

[0016] The metal organic framework material of the present invention is prepared by directly preparing aromatic organic ligands and metal organic salts by a solvent-free continuous mechanical method, and is specifically prepared by the following method: the aromatic organic ligands and metal organic salts are melt-blended, extruded and granulated to obtain the metal organic framework material. Specifically, the aromatic organic ligands and the metal organic salts are mixed for 20 min to 40 min, and then the mixed materials are melt-blended, extruded and granulated in a twin-screw extruder to obtain the metal organic framework material. In certain embodiments of the present invention, the aromatic organic ligands and the metal organic salts are mixed and uniformly mixed, and gradually added to the preheated twin-screw extruder from the addition port for melt-blending, extrusion and granulation, and the extrusion product is collected at the discharge port, water-cooled, granulated, separated, washed, and dried to obtain the metal organic framework material. The present invention does not specifically limit the specific method of the above separation, and can be a separation method well known to those skilled in the art, including but not limited to centrifugation or filtration. The washing of the present invention is preferably carried out with anhydrous ethanol.

[0017] The temperature of the melt blending extrusion granulation of the present invention is 180°C to 200°C, the extrusion pressure of the melt blending extrusion granulation is 300 pst to 900 pst, and the melt blending extrusion granulation is carried out at a rotation speed of 100 rpm to 300 rpm. In certain embodiments of the present invention, a twin-screw extruder is used for the melt blending extrusion granulation, the extrusion pressure of the twin-screw extruder is controlled to be 300 pst to 900 pst, the rotation speed of the twin-screw extruder is controlled to be 100 rpm to 300 rpm, the five-stage temperature of the twin-screw extruder is controlled to be 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, and the head temperature of the twin-screw extruder is 190±5°C.

[0018] The metal organic framework material of the present invention has a three-dimensional pore structure and an aromatic ring structure. The three-dimensional pore structure and the substituted heteroatoms in the aromatic ring respectively enhance the scattering effect of X-rays and strengthen the absorption of X-ray photoelectrons, which can significantly improve the development effect of implantable materials and can be used in the preparation of CT developer. At the same time, the substituted heteroatoms and the substituted groups in the aromatic ring structure can also improve the interface compatibility between the metal organic framework material and the polymer matrix, so that the mechanical properties of the implantable material prepared by using the same are optimized. At the same time, based on its development effect, it can be used to prepare implantable materials with X-ray development function.

[0019] The present invention provides an implantable material, comprising a high molecular polymer matrix and a metal organic framework material doped in the high molecular polymer matrix;

[0020] The metal organic framework material comprises an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand;

[0021] The aromatic organic ligand is selected from compounds having a structure of Formula I or Formula II;

[0022] Formula I; Formula II;

[0023] Wherein, the X1 is selected from O or S;

[0024] Said X2 and X3 are independently selected from C or N;

[0025] The R1, R2, R3 and R4 are independently selected from H, a substituted or unsubstituted C1-C5 alkyl group.

[0026] Preferably, the aromatic organic ligand of the present invention is selected from compounds having a structure of Formula Ia or Formula II-a;

[0027] Formula Ia; Formula II-a.

[0028] Preferably, X2 and X3 are different; and R1, R2, R3 and R4 are independently selected from one of hydrogen, methyl and ethyl.

[0029] In certain embodiments of the present invention, the aromatic organic ligand is selected from one or more of 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, 2,5-furandicarboxylic acid dimethyl ester, 2,5-thiophenedicarboxylic acid dimethyl ester, 2,6-pyridinedicarboxylic acid dimethyl ester and 3,5-pyridinedicarboxylic acid dimethyl ester. In certain embodiments of the present invention, the coordinated metal atom is selected from one or more of hafnium, zirconium or bismuth. In certain embodiments of the present invention, the high molecular polymer matrix is ​​obtained from one or more of polyurethane, nylon and nylon elastomer.

[0030] The implantable material provided by the present invention is an implantable material with X-ray development function, which includes a polymer matrix and a metal organic framework material doped in the polymer matrix; the metal organic framework material includes an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand; wherein the metal organic framework material has a three-dimensional pore structure and an aromatic ring structure, and its three-dimensional pore structure and the substituted heteroatoms in the aromatic ring respectively play a role in enhancing the scattering effect of X-rays and strengthening the absorption of X-ray photoelectrons, which can significantly improve the development effect of the implantable material. At the same time, the substituted heteroatoms and their substituted groups in the aromatic ring structure also improve the interface compatibility between the metal organic framework material and the polymer matrix, so that the mechanical properties of the implantable material are optimized. The doping amount of the metal organic framework material in the polymer matrix of the present invention is 10 wt%~40 wt%.

[0031] The present invention also provides a method for preparing an implantable material as described in any of the above technical solutions. The method for preparing an implantable material provided by the present invention directly prepares an implantable material from aromatic organic ligands, metal organic salts and high molecular polymer materials by a solvent-free one-step continuous mechanical method, specifically comprising the following steps: melt-blending, extruding and granulating the aromatic organic ligands, metal organic salts and high molecular polymer materials to obtain an implantable material.

[0032] More specifically, the aromatic organic ligand, the metal organic salt and the high molecular polymer material are mixed for 20 min to 40 min, and then the mixed material is melt-blended, extruded and granulated in a twin-screw extruder to obtain an implantable material. In certain embodiments of the present invention, the aromatic organic ligand, the metal organic salt and the high molecular polymer material are mixed for 20 min to 40 min, and gradually added to the preheated twin-screw extruder from the addition port, and the extruded product is collected at the discharge port, water-cooled, granulated, separated, washed, and dried to obtain an implantable material. The present invention does not specifically limit the specific method of the above separation, and can be a separation method well known to those skilled in the art, including but not limited to centrifugation or filtration. The washing described in the present invention is preferably carried out with anhydrous ethanol. The implantable material obtained by the preparation method provided by the present invention is a granular material, which can be further processed into a film material later.

[0033] The temperature of the melt blending extrusion granulation of the present invention is 190°C to 230°C, the extrusion pressure of the melt blending extrusion granulation is 300 pst to 900 pst, and the melt blending extrusion granulation is carried out at a rotation speed of 100 rpm to 300 rpm. In certain embodiments of the present invention, a twin-screw extruder is used for the melt blending extrusion granulation, the extrusion pressure of the twin-screw extruder is controlled to be 300 pst to 900 pst, the rotation speed of the twin-screw extruder is controlled to be 100 rpm to 300 rpm, the five-stage temperature of the twin-screw extruder is controlled to be 200±5°C, 220±5°C, 220±5°C, 220±5°C, 220±5°C, and 220±5°C, respectively, and the head temperature of the twin-screw extruder is 220±10°C.

[0034] In the preparation method of the implantable material of the present invention, the mass ratio of the aromatic organic ligand and the metal organic salt is (1-6):1, preferably (3-5):1; the ratio of the total mass of the aromatic organic ligand and the metal organic salt to the mass of the high molecular polymer material is 1:(2-15), preferably 1:(2.5-10). The present invention can adjust the metal organic framework doping amount from 10 wt% to 40 wt% by changing the feed ratio of the total mass of the aromatic organic ligand and the metal organic salt to the mass of the high molecular polymer material.

[0035] In the preparation method of the implantable material of the present invention, the metal organic salt is selected from one or more of hafnium basic carbonate, zirconium basic carbonate, bismuth basic carbonate, hafnium acetylacetonate, zirconium acetylacetonate, bismuth acetylacetonate, hafnium acetate, zirconium acetate, and bismuth acetate, preferably selected from one or more of hafnium basic carbonate, zirconium basic carbonate, and bismuth basic carbonate. The high molecular polymer material is selected from one or more of polyurethane, nylon, and nylon elastomer. The aromatic organic ligand is the same as above and will not be repeated.

[0036] The present invention also provides an implantable interventional device, which is made of the implantable interventional material described in any of the above technical solutions; or, it is made of the implantable interventional material obtained by the preparation method described in any of the above technical solutions. The implantable interventional device of the present invention is made based on the implantable interventional material, and the implantable interventional material has an enhanced X-ray development function. Compared with the barium sulfate-based developer, the composite material has the advantages of high X-ray development resolution, good mechanical properties, good biocompatibility, etc., and can be used to prepare implantable medical devices including but not limited to heart stents, central venous catheters, indwelling needles, etc.

[0037] The present invention provides the application of metal organic framework materials in the preparation of development functional materials, implantable intervention materials and preparation methods thereof, and implantable intervention devices. The metal organic framework material of the present invention has an enhanced X-ray development function, can be applied to the preparation of CT contrast agents, and has excellent water and thermal stability and good biocompatibility. When applied to the preparation of implantable intervention materials, the obtained implantable intervention materials not only have X-ray development functions, but also inherit the properties of excellent water and thermal stability and good biocompatibility, making it possible to select a variety of subsequent processing methods and to apply them in in vivo implantable intervention scenarios.

[0038] The implantable material provided by the present invention has excellent X-ray attenuation ability, and shows a better development effect than commercially available barium sulfate and iodine-containing compounds. It has high X-ray development resolution, good mechanical properties, and good biocompatibility. It can maintain the mechanical properties and processing properties of the original polymer matrix, and synergistically solve the contradictory relationship between the development effect and mechanical processing properties of current medical developers. At the same time, the solvent-free continuous mechanical preparation method of the implantable material of the present invention does not use organic solvents such as N, N-dimethylformamide used in traditional solvent thermal metal-organic framework synthesis, and the production capacity is not controlled by the reactor capacity. The method is simple to operate, green and environmentally friendly, mild reaction conditions, high synthesis efficiency, low cost, and can meet the requirements of industrial scale preparation. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 The physical pictures of the composite film prepared in Examples 2, 3 and 6;

[0040] Figure 2 It is a statistical diagram of X-ray development effects of MOFs nanoparticles and nano-hafnium oxide particles prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0041] Figure 3 The actual objects and corresponding X-ray development images of the composite materials of pure polyurethane, hafnium oxide and MOFs particles prepared in Example 2, Comparative Example 1 and Comparative Example 2;

[0042] Figure 4 This is a scanning electron microscope (SEM) photograph of the hafnium-based metal organic framework material prepared in Example 1;

[0043] Figure 5 This is a graph showing the cell compatibility test of the hafnium-based metal-organic framework material prepared in Example 1. DETAILED DESCRIPTION

[0044] The present invention discloses the application of metal organic framework materials in the preparation of developing functional materials, implantable materials and preparation methods thereof, and implantable devices. Those skilled in the art can refer to the contents of this article and appropriately improve the process parameters for implementation. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all deemed to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously modify or appropriately change and combine the methods and applications of this article without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention.

[0045] The present invention will be further described below in conjunction with embodiments:

[0046] Example 1

[0047] Preparation of furanyl hafnium metal organic framework materials:

[0048] 5 parts of hafnium basic carbonate and 1 part of 2,5-furandicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, respectively, the head temperature is 190±5°C, and after extrusion, the metal organic framework material with X-ray development performance is obtained after ethanol washing.

[0049] Example 2

[0050] Preparation of furanyl hafnium metal organic framework composites:

[0051] 5 parts of hafnium carbonate basic, 1 part of 2,5-furandicarboxylic acid and 12 parts of M875H polyurethane material are added to a high-speed mixer and mixed for 60 minutes; the mixed pellets are added to a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5℃, 220±5℃, 220±5℃, 220±5℃, 220±5℃, and the head temperature is 220±5℃. After extrusion, water cooling and granulation are performed to obtain an implant composite material with an X-ray development performance of 10wt% MOFs weight percentage.

[0052] Example 3

[0053] Preparation of furanyl hafnium metal organic framework composites:

[0054] 5 parts of hafnium carbonate basic, 1 part of 2,5-furandicarboxylic acid and 7 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 60 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5°C, 220±5°C, 220±5°C, 220±5°C, 220±5°C, and the head temperature is 220±5°C, and after extrusion, water cooling and granulation, an implant composite material with an MOFs weight percentage of 30wt% and X-ray development performance is obtained.

[0055] Example 4

[0056] Preparation of furanyl hafnium metal organic framework composites:

[0057] 5 parts of hafnium basic carbonate, 1 part of 2,5-furandicarboxylic acid and 7 parts of PEBAX nylon elastomer material are added to a high-speed mixer and mixed for 60 minutes; the mixed pellets are added to a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 220±5℃, 225±5℃, 220±5℃, 220±5℃, 225±5℃, and the head temperature is 220±5℃. After extrusion, water cooling and granulation are performed to obtain an implant composite material with an X-ray development performance of 30wt% MOFs weight percentage.

[0058] Example 5

[0059] Preparation of thienyl hafnium metal organic framework materials:

[0060] 5 parts of hafnium basic carbonate and 1 part of 2,5-thiophenedicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, the head temperature is 190±5°C, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0061] Example 6

[0062] Preparation of thiophene-based hafnium metal-organic framework composites:

[0063] 5 parts of hafnium carbonate basic, 1 part of 2,5-thiophenedicarboxylic acid and 7 parts of M875H polyurethane material are added to a high-speed mixer and mixed for 60 minutes; the mixed pellets are added to a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5℃, 220±5℃, 220±5℃, 220±5℃, 220±5℃, and the head temperature is 220±5℃. After extrusion, water cooling and granulation are performed to obtain an implant composite material with an MOFs weight percentage of 30 wt% and X-ray development performance.

[0064] Example 7

[0065] Preparation of thiophene-based hafnium metal-organic framework composites:

[0066] 5 parts of hafnium carbonate basic, 1 part of 2,5-thiophenedicarboxylic acid and 7 parts of PEBAX nylon elastomer material are added to a high-speed mixer and mixed for 60 minutes; the mixed pellets are added to a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 220±5℃, 225±5℃, 220±5℃, 220±5℃, 225±5℃, and the head temperature is 220±5℃. After extrusion, water cooling and granulation are performed to obtain an implant composite material with an X-ray development performance of 30 wt% of MOFs weight percentage.

[0067] Example 8

[0068] Preparation of pyridyl hafnium metal organic framework materials:

[0069] 5 parts of hafnium basic carbonate and 1 part of 3,5-pyridinedicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, the head temperature is 190±5°C, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0070] Example 9

[0071] Preparation of pyridyl hafnium metal organic framework composite materials:

[0072] 5 parts of hafnium carbonate basic, 1 part of 3,5-pyridinedicarboxylic acid and 7 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 60 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5℃, 220±5℃, 220±5℃, 220±5℃, 220±5℃, and the head temperature is 220±5℃, and after extrusion, water cooling and granulation are performed to obtain an implant composite material with an X-ray development performance of 30 wt% of MOFs weight percentage;

[0073] Example 10

[0074] Preparation of pyridyl hafnium metal organic framework composite materials:

[0075] 5 parts of hafnium carbonate basic, 1 part of 2,6-pyridinedicarboxylic acid and 7 parts of PEBAX nylon elastomer material are added to a high-speed mixer and mixed for 60 minutes; the mixed pellets are added to a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 220±5℃, 225±5℃, 220±5℃, 220±5℃, 225±5℃, and the head temperature is 220±5℃. After extrusion, water cooling and granulation are performed to obtain an implant composite material with an X-ray development performance of 30 wt% of MOFs weight percentage.

[0076] Embodiment 11

[0077] Preparation of furanyl zirconium metal organic framework materials:

[0078] 5 parts of basic zirconium carbonate and 1 part of 2,5-furandicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5℃, 195±5℃, 200±5℃, 200±5℃, 195±5℃, the head temperature is 190±5℃, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0079] Example 12

[0080] Preparation of furanyl bismuth metal organic framework materials:

[0081] Four parts of bismuth subcarbonate and one part of 2,5-furandicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, respectively, the head temperature is 190±5°C, and after extrusion, the metal organic framework material with X-ray development performance is obtained after ethanol washing.

[0082] Example 13

[0083] Preparation of furan-based multi-metal organic framework materials:

[0084] 2.5 parts of basic zirconium carbonate, 2.5 parts of basic hafnium carbonate and 1 part of 2,5-furandicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5℃, 195±5℃, 200±5℃, 200±5℃, 195±5℃, respectively, the head temperature is 190±5℃, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0085] Embodiment 14

[0086] Preparation of furan-based multi-metal organic framework materials:

[0087] 1 part of zirconium basic carbonate, 2 parts of hafnium basic carbonate, 2 parts of bismuth basic carbonate and 1 part of 2,5-furandicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5℃, 195±5℃, 200±5℃, 200±5℃, 195±5℃, the head temperature is 190±5℃, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0088] Embodiment 15

[0089] Preparation of furan-based multi-metal organic framework composites:

[0090] 2 parts of basic zirconium carbonate, 3 parts of basic hafnium carbonate, 1 part of 2,5-furandicarboxylic acid and 9 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 60 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5°C, 220±5°C, 220±5°C, 220±5°C, 220±5°C, and the head temperature is 220±5°C, and after extrusion, water cooling and granulation, an implant composite material with an MOFs weight percentage of 30 wt% and X-ray development performance is obtained.

[0091] Example 16

[0092] Preparation of mixed ligand hafnium-based metal organic framework materials:

[0093] 5 parts of hafnium carbonate basic, 0.5 parts of 2,5-furandicarboxylic acid and 0.5 parts of 2,5-thiophenedicarboxylic acid are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending and extrusion granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 185±5°C, 195±5°C, 200±5°C, 200±5°C, 195±5°C, respectively, the head temperature is 190±5°C, and after extrusion, the metal organic framework material with X-ray development performance is obtained after washing with ethanol.

[0094] Embodiment 17

[0095] Preparation of mixed ligand hafnium-based metal-organic framework composites:

[0096] 5 parts of hafnium carbonate basic, 0.3 parts of 2,5-furandicarboxylic acid, 0.7 parts of 2,6-pyridinedicarboxylic acid and 9 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 60 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5℃, 220±5℃, 220±5℃, 220±5℃, 220±5℃, and the head temperature is 220±5℃, and after extrusion, water cooling and granulation, an implant composite material with X-ray development performance having a weight percentage of MOFs of 30 wt% is obtained.

[0097] Comparative Example 1

[0098] The blank group was prepared by pressing M875H polyurethane material into tablets.

[0099] Comparative Example 2

[0100] 3 parts of basic hafnium carbonate and 7 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 3 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5℃, 220±5℃, 220±5℃, 220±5℃, 220±5℃, and the head temperature is 220±5℃, and after extrusion, water cooling and granulation, a composite material with a weight percentage of hafnium oxide of 30 wt% is obtained.

[0101] Comparative Example 3

[0102] 3 parts of 2,5-furandicarboxylic acid and 7 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 30 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5°C, 220±5°C, 220±5°C, 220±5°C, 220±5°C, and the head temperature is 220±5°C, and after extrusion, water cooling and granulation are performed to obtain a composite material containing an organic ligand.

[0103] Comparative Example 4

[0104] 3 parts of barium sulfate and 7 parts of M875H polyurethane material are added into a high-speed mixer and mixed for 3 minutes; the mixed pellets are added into a twin-screw extruder for melt blending, extrusion and granulation, the extrusion pressure of the twin-screw extruder is 300 to 900 pst, the extruder speed is 100 to 300 rpm, the temperature settings of each working section of the twin-screw extruder are 200±5°C, 220±5°C, 220±5°C, 220±5°C, 220±5°C, and the head temperature is 220±5°C, and after extrusion, water cooling and granulation, a composite material with a weight percentage of 30wt% of barium sulfate is obtained.

[0105] The above-mentioned materials can be made into thin films, such as Figure 1 As shown, Figure 1 This is a physical picture of the composite film prepared in Examples 2, 3, and 6.

[0106] The test results of the implant composite materials of X-ray imaging performance obtained in Examples 3, 4, 6, 7, 9, and 10 and the test results of the composite materials obtained in Comparative Examples 1 to 3 are shown in Table 1:

[0107] Table 1

[0108]

[0109] X-ray imaging effect statistics:

[0110] Ultrapure water was used as a dispersant to gradiently dilute the developer material to obtain a series of developer material / water dispersions with concentrations of 40-20-10-5-2.5 mg / mL. Micro CT was used to scan metal organic framework material aqueous solutions of different concentrations at 50 kV and 90Kv to obtain the HU value, which reflects the X-ray attenuation effect of the material. The HU value has a good linear relationship with the sample size of the metal organic framework material. Examples 1 to 6 and Comparative Examples 1 to 3 prove that the introduction of metal organic framework material pores causes secondary scattering attenuation of X-rays, and the development effect is enhanced. Figure 2 and Figure 3 As shown, Figure 2 It is a statistical diagram of X-ray development effects of MOFs nanoparticles and nano-hafnium oxide particles prepared in Example 1, Comparative Example 1 and Comparative Example 2; Figure 3 The actual objects and corresponding X-ray development images of the pure polyurethane, hafnium oxide and MOFs particle composite materials prepared in Example 2, Comparative Example 1 and Comparative Example 2.

[0111] Hemolysis test:

[0112] Fresh rabbit red blood cells were obtained by centrifugation. The red blood cells were first diluted with 0.9% NaCl to form a 5% red blood cell suspension, and then 1 cm×1 cm of the membrane material prepared in Example 1 was added to 1 mL of the 5% red blood cell suspension and incubated at 37°C for 1 h. 50 μL of red blood cells were added to 1 mL of distilled water and 0.9% NaCl as positive and negative controls, respectively. After incubation, centrifuge at 2000 rpm for 5 min, take the blood cells, and transfer the supernatant to a 96-well plate. The optical density (OD) of hemoglobin was measured at 540 nm. The results are shown in Figure 2. Figure 4 As shown, Figure 4 This is a scanning electron microscope (SEM) photograph of the hafnium-based metal organic framework material prepared in Example 1. Conclusion: Neither the pure TPU membrane nor the MOFs / TPU membrane (Example 1) causes hemolysis, which proves that the composite material has good blood compatibility.

[0113] Biocompatibility test:

[0114] The cell counting kit-8 (CCK-8) method was used to detect the in vitro cell compatibility of the composite membrane. L929 mouse fibroblasts were cultured in Dulbecco's Modified Eagle Medium (H,DMEM) containing 10% volume fraction of fetal bovine serum. First, 100 μL of cells were taken at a density of 1 × 10 4 cells / mL in a 96-well plate, incubated at 37°C and 5% CO2 for 24 hours, and irradiated with UV light for 1 hour. Then extract in DMEM containing 10% volume fraction of fetal bovine serum, and extract at 37°C for 24 hours. After removing the original culture medium, add 100 μL of leaching solution with different sample series concentration gradients (100, 75, 50, 25, 10%), culture for 24 hours, remove the culture medium, and wash twice with PBS. Add 100 μL of culture medium containing 10% CCK-8, culture for 2 hours, and measure OD at 450 nm. In addition, the blank control without sample is the negative control, and the group without cells is the positive control, and the cell viability is calculated. The results are shown in Figure 5 As shown, Figure 5 This is a test diagram of the cell compatibility of the hafnium-based metal organic framework material prepared in Example 1. Conclusion: Both the pure polyurethane membrane and the composite membrane (Example 1) will not cause cell apoptosis, which proves that the composite material has good cell compatibility.

[0115] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. The use of metal organic framework materials in the preparation of CT contrast agents or implantable materials with X-ray imaging function, characterized in that: The metal organic framework material comprises an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand; The aromatic organic ligand is selected from compounds having a structure of Formula I or Formula II; Formula I; Formula II; Wherein, the X1 is selected from O or S; Said X2 and X3 are independently selected from C or N; The R1, R2, R3 and R4 are independently selected from H, a substituted or unsubstituted C1-C5 alkyl group.

2. The use according to claim 1, characterized in that: The aromatic organic ligand is selected from one or more of 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, 2,5-furandicarboxylic acid dimethyl ester, 2,5-thiophenedicarboxylic acid dimethyl ester, 2,6-pyridinedicarboxylic acid dimethyl ester and 3,5-pyridinedicarboxylic acid dimethyl ester; The coordinating metal atom is selected from one or more of hafnium, zirconium or bismuth.

3. The use according to claim 1 or 2, characterized in that: The metal organic framework material is prepared by the following method: The aromatic organic ligand and the metal organic salt are melt-blended, extruded and granulated to obtain the metal organic framework material.

4. An implantable material, characterized in that: It includes a high molecular polymer matrix and a metal organic framework material doped in the high molecular polymer matrix; The metal organic framework material comprises an aromatic organic ligand and a coordinated metal atom on the aromatic organic ligand; The aromatic organic ligand is selected from compounds having a structure of Formula I or Formula II; Formula I; Formula II; Wherein, the X1 is selected from O or S; Said X2 and X3 are independently selected from C or N; The R1, R2, R3 and R4 are independently selected from H, a substituted or unsubstituted C1-C5 alkyl group.

5. The implant material according to claim 4, characterized in that: The aromatic organic ligand is selected from one or more of 2,5-furandicarboxylic acid, 2,5-thiophenedicarboxylic acid, 2,6-pyridinedicarboxylic acid, 3,5-pyridinedicarboxylic acid, 2,5-furandicarboxylic acid dimethyl ester, 2,5-thiophenedicarboxylic acid dimethyl ester, 2,6-pyridinedicarboxylic acid dimethyl ester and 3,5-pyridinedicarboxylic acid dimethyl ester; The coordinating metal atom is selected from one or more of hafnium, zirconium or bismuth; The high molecular polymer matrix is ​​obtained from one or more of polyurethane, nylon and nylon elastomer.

6. The implant material according to claim 4 or 5, characterized in that: The doping amount of the metal organic framework material in the high molecular polymer matrix is ​​10 wt% to 40 wt%.

7. The method for preparing an implantable material according to any one of claims 4 to 6, characterized in that: The following steps are involved: The aromatic organic ligand, the metal organic salt and the high molecular polymer material are melt-blended, extruded and granulated to obtain the implantable material.

8. The method for preparing an implantable material according to claim 7, characterized in that: The metal organic salt is selected from one or more of hafnium basic carbonate, zirconium basic carbonate, bismuth basic carbonate, hafnium acetylacetonate, zirconium acetylacetonate, bismuth acetylacetonate, hafnium acetate, zirconium acetate, and bismuth acetate; The high molecular polymer material is selected from one or more of polyurethane, nylon and nylon elastomer.

9. The method for preparing an implantable material according to claim 7, characterized in that: The mass ratio of the aromatic organic ligand to the metal organic salt is (1-6):1; The ratio of the total mass of the aromatic organic ligand and the metal organic salt to the mass of the high molecular polymer material is 1:(2-15).

10. An implantable interventional device, characterized in that: Made from the implantable material described in any one of claims 4 to 6; or, made from the implantable material obtained by the preparation method described in any one of claims 7 to 9.